A myelopoiesis gene signature during remission in anti‐neutrophil cytoplasm antibody‐associated vasculitis does not predict relapses but seems to reflect ongoing prednisolone therapy. (February 2014) - Kurz, T.; Weiner, M.; Skoglund, C.; Basnet, S.; Eriksson, P.; Segelmark, M.
Summary A myelopoiesis gene signature in circulating leucocytes, exemplified by increased myeloperoxidase (MPO) and proteinase 3 (PR3) mRNA levels, has been reported in patients with active anti‐neutrophil cytoplasm antibody‐associated vasculitis (AAV), and to a lesser extent during remission. We hypothesized that this signature could predict disease relapse. mRNA levels of PR3, MPO, selected myelopoiesis transcription factors [CCAAT/enhancer binding protein α (CEBP‐α), CCAAT/enhancer binding protein β (CEBP‐β), SPI1/PU.1‐related transcription factor (SPIB), spleen focus forming virus proviral integration oncogene, PU.1 homologue (SPI1)] and microRNAs (miRNAs) from patient and control peripheral blood mononuclear cells (PBMC) and polymorphonuclear cells (PMN) were analysed and associated with clinical data. Patients in stable remission had higher mRNA levels for PR3 (PBMC, PMN) and MPO (PBMC). PR3 and SPIB mRNA correlated positively in controls but negatively in patient PBMC. Statistically significant correlations existed between PR3 mRNA and several miRNAs in controls, but not in patients. PR3/MPO mRNA levels were not associated with previous or future relapses, but correlated with steroid treatment. Prednisolone doses were negatively linked to SPIB and miR‐155‐5p, miR‐339‐5p (PBMC) and to miR‐221, miR‐361 and miR‐505 (PMN). PR3 mRNA in PBMC correlated with time since last flare, blood leucocyte count and estimated glomerular filtration rate. Our results show that elevated leucocyte PR3 mRNA levels in AAV patients in remission do not predict relapse. The origin seems multi‐factorial, but to an important extent explainable by prednisolone action. Gene signatures in patients with AAV undergoing steroid treatment should therefore be interpreted accordingly.